Effectiveness of Chulalongkorn-Vestibular-Balance- Exercise in patients with acute post-operative vestibular schwannoma - Utoomprurkporn, Nattawan; Patarapak, Saowaros (Chulalongkorn Medical Journal, 2023)
Background : Post-operative patients after removal of vestibular schwannoma usually suffer from dizziness and vertigo. So far, there is no well-established rehabilitation program to help these patients. Chulalongkorn-Vestibular- Balance-Exercise Program is hence designed to as a rehabilitation program that stimulates improvement of the vestibular function. The program should help relieve the undesirable symptoms in these patients. Objective : To study the effect of Chulalongkorn-Vestibular-Balance-Exercise Program in improving vestibular compensation in patients with post-operative vestibular schwannoma removal at 1 month after the operation. Methods : Patients with vestibular schwannoma and admitted for surgery at King Chulalongkorn Memorial Hospital were recruited. They were explained about the study and signed their informed consent forms prior to surgery and then randomized into 2 groups: exercise group and control group. Chulalongkorn-Vestibular-Balance-Exercise Program has simplified both vestibular adaptation exercises (x1 viewing paradigm and 2 viewing paradigm) and habituation exercises into five illustrated, simple steps that can be performed at home after discharge. Both groups were assessed at one month post-operation; their scores were in 2 aspects: the subjective symptom of vertigo/ disequilibrium (visual analog score; VAS 0 - 10); the objective measure of imbalance (posturography). Results : In the exercise group, visual analog score in vertigo/disequilibrium postoperation was 1.3/10 compared to 4.5/10 in control group at 1 month. Posturogram showed improvement in objective measurement in condition 5 (use only vestibular clue) increased 23.53% from controls. Conclusion : Despite its simplicity, Chulalongkorn-Vestibular-Balance-Exercise Program can effectively enhance vestibular compensation, as seen in the trend of improvement in patients’ balance status and vertigo/disequilibrium symptoms in post-operative vestibular schwannoma patients at as early as one month.